Machine Learning and Knowledge Discovery in Databases - Daelemans, Walter (H: Springer, 2017)
This book constitutes the refereed proceedings of the joint conference on Machine Learning and Knowledge Discovery in Databases: ECML PKDD 2008, held in Antwerp, Belgium, in September 2008.